Organizational crime and corruption in Brazil a case study of the "Operation Carwash" court records - Valarini, Elizângela; Pohlmann, Markus (International journal of law, crime and justice, 2019)
This paper aims to examine the informal mechanisms and factors of corporate crime in Brazil that contribute to the persistence of political corruption. For this analysis, official records, e.g. closed criminal trials produced by Operation Carwash, one of the biggest cases of white-collar crime and political corruption in Brazil's history, will be used. The focus of the analysis is on the criminal trials, generated in the early phases of the investigation, which revealed the illegal activities of large Brazilian construction companies as well as its cartel-building to defraud the Petrobras' contracts. The analysis on the modus operandi of this cartel served to reconstruct the unwritten rules inside organizations that are involved in the bribery-scheme. The analysis showed that Brazilian private enterprises, represented by its senior executives and top managers, used the lack of regulation and informal rules, rooted in the political system, to achieve illegal profits.